Pertumbuhan Bibit Kelapa Sawit (Elais guineensis) pada Beberapa Waktu dan Arah Aplikasi Boron (B) dan Silikon (Si) Melalui Daun - Kaloko, Ageng; Susila, Eka Tarwaca; Dewa, Didik Indra (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2015)
Study entitled Growth and Drought Resistance Seed Oil Palm (Elaeis guineensis) in Multiple Time and Direction Applications Boron (B) and Silicon (Si) through Leaves aims to study the effect of B and Si on physiological processes and growth of oil palm seedlings experiencing drought stress and get a way and timing of B and Si is effective to reduce the effect of drought on the decline of physiological processes and growth of oil palm seedlings, Has been implemented in the hamlet Bendosari Madurejo village, Prambanan subdistrict, Sleman; Laboratory of Plant Sciences Faculty of Agriculture, Plant Anatomy Laboratory of the Faculty of Biology and Integrated Research and Testing Laboratory (LPPT) Gadjah Mada University Yogyakarta in March to December of 2012. Research using a complete randomized block design (RAKL) factorial 3 x 3 1 to 3 blocks as replications. The first factor is the way fertilization, the second factor is the time of fertilization and added a comparison (control) without any fertilization treatment. The data analyzed were obtained using Varian Analysis (ANOVA) at the level of 5%, and followed by a test of least significant difference LSD. The results showed that the uptake and increased significantly with the application and the leaves by spraying in the morning, afternoon and evening through the direction of the bottom surface, the top and bottom of leaves. However, absorption of Si is only able to increase if the source of Si fertilizer applied by spraying the leaves through a downward direction on the surface of leaves in the evening. Oil palm seedlings can be improved resistance to drought stress with an indication of the form of increasing scores lignin and suberin in roots network as well as the size of the diameter of the rod when compared with control through the application of fertilizer source of B and Si on the leaves by spraying in the morning, afternoon and evening through direction of the bottom surface, the top and bottom of leaves.